THE RELATIONSHIP BETWEEN PREECLAMPSIA RISK FACTORS AND THE INCIDENCE OF LOW BIRTH WEIGHT (LBW) BABIES AT ARUN LHOKSEUMAWE HOSPITAL, LHOKSEUMAWE CITY - Endang Putri Lestari; Siti Nurmawan Sinaga; Yesica Geovany Sianipar; Zulkarnain Batu Bara; Dwi Gita Sabrina; Jasica Pratini; Valentina Sari Theresia Siagian (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
This study aims to determine the relationship between preeclampsia risk factors and the incidence of low birth weight (LBW) babies at Arun Lhokseumawe Hospital, Lhokseumawe City, Aceh Province in 2024, with the background that LBW is still a major public health problem in Indonesia and the world, which contributes greatly to infant morbidity, mortality, and disability, and is one of the important indicators in the Sustainable Development Goals (SDGs) and the National Medium-Term Development Plan (RPJMN). Based on data from WHO and the Indonesian Ministry of Health, LBW is the main cause of neonatal death in Indonesia, with the proportion of infant deaths due to LBW reaching 32.2% in 2020. Preeclampsia, which is a pregnancy disorder characterized by hypertension, edema, and proteinuria, is one of the main causes of LBW because it can inhibit fetal growth due to impaired blood flow and nutrition to the placenta. This study uses a quantitative approach with a cross-sectional design, with a population of all mothers giving birth at Arun Lhokseumawe General Hospital in the period January-April 2024, and samples were taken based on medical record data, where 10 cases of LBW were found, 5 of which had a history of preeclampsia. The variables analyzed included maternal age, parity, and anemia as risk factors for preeclampsia, and their relationship with the incidence of LBW. The results of this study are expected to provide theoretical contributions as a reference for the development of obstetrics, scientific benefits for further research, and practical benefits for hospitals in improving the quality of services, especially the prevention and treatment of preeclampsia to reduce the incidence of LBW. Initial findings and literature reviews indicate a significant relationship between preeclampsia and the incidence of LBW, in line with previous studies stating that pregnant women with preeclampsia have a higher risk of giving birth to babies with low birth weight, so that early detection efforts, education, and appropriate interventions are needed to reduce this risk and improve the health of mothers and babies in the future.